Ten Theses on the Concept of Addiction in the Work of Deleuze and Guattari (Palimpsesto, 2023)
The present writing proposes, in ten theses built through the Nietzschean method of dramatization, that all use, consumption or activity, can be conceived as a machine that is mounted on a line of flight of an individual or a group, subjectifying, singling out and increasing the power. But addiction can also set up a capture device capable of subtracting power, dominating one's life, and destroying the entire existential territory, at the same time that it serves -paradoxically- to stabilize current societies. It is concluded that an addiction machine is productive when it is regulated by means of a plan based on an ethic of prudence; that is, when it is in favor of life.
Keywords: Addiction; Drug; Machine; Line of flight; Capture device